2019
DOI: 10.1097/md.0000000000015711
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews of pharmacological and nonpharmacological treatments for patients with chronic urticaria

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…[ 38 , 39 ] Numerous studies have confirmed that moxibustion therapy is effective in treating CSU. [ 20 , 29 ] Given that no relevant systematic reviews and meta-analysis have been carried out, we set out to prove the effect of moxibustion therapy for CSU, to provide a more reasonable and effective treatment plan for CUS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 38 , 39 ] Numerous studies have confirmed that moxibustion therapy is effective in treating CSU. [ 20 , 29 ] Given that no relevant systematic reviews and meta-analysis have been carried out, we set out to prove the effect of moxibustion therapy for CSU, to provide a more reasonable and effective treatment plan for CUS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Wormwood has the effect of warming meridians and dispelling cold, and can dispel dampness and relieve itching used externally. [ 19 ] According to modern mechanism studies, moxibustion therapy has antiallergic effects and can treat a variety of diseases related to allergic reactions, including urticaria, allergic rhinitis, irritable bowel syndrome, [ 20 22 ] etc. Moxibustion therapy also has antibacterial effects, which can inhibit various bacteria such as gram-negative bacteria, Streptococcus beta , Pseudomonas aeruginosa , etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urticaria is a very common inflammatory dermatosis; its diagnosis is based on history and clinical examination 1 . It is a complex multifactorial pathology involving genetic and environmental factors 2,3 . Due to its multiple etiologies and morphological variants, this pathology can be subject to numerous diagnostic errors and therefore to inadequate treatment, in particular by nonspecialized personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that urticaria is a frequent pathology either in developed or in developing countries, it is essential to know the various aspects of its diagnosis and management to avoid the occurrence of complications. Many triggering factors of urticaria are found in literature, including cold, heat, solar, delayed pressure, vibratory, insect bites, dermographic, aquagenic, cholinergic, contact, and exercise 2,3,9 …”
Section: Introductionmentioning
confidence: 99%